Regression models for unconstrained, partially or fully constrained continuation odds ratios - Cole, Stephen R; Ananth, Cande V (International journal of epidemiology, 2001)
Epidemiologists frequently encounter studies with ordered responses. Standard ordered response logit models, such as the continuation ratio model, constrain exposure to have a homogenous effect across thresholds of the ordered response. We demonstrate a method for fitting regression models for unconstrained, partially or fully constrained continuation odds ratios using a ‘person-threshold’ data set. For each subject, we create a separate record for each response threshold the subject is ‘at risk’ of passing and then apply standard binary logistic regression to estimate the continuation-ratio model. An example demonstrates the unconstrained, partially and fully constrained continuation-ratio model, while a small simulation study examines some properties of the proposed ‘person-threshold’ approach. Finally, we present a brief discussion of statistical software to implement the method.